2008
DOI: 10.2106/jbjs.f.01324
|View full text |Cite
|
Sign up to set email alerts
|

Endoprosthetic Reconstruction for the Treatment of Musculoskeletal Tumors of the Appendicular Skeleton and Pelvis

Abstract: We believe these medium to long-term results with first-generation endoprostheses are encouraging and justify the continued use of endoprostheses for reconstruction following the excision of a bone tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
177
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(201 citation statements)
references
References 11 publications
8
177
2
2
Order By: Relevance
“…Currently, it is not possible to avoid periprosthetic infection completely, despite the use of systemic antibiotic treatment, operating rooms with laminar airflow, and routine screening for methicillin-resistant Staphylococcus aureus (MRSA). In the literature, overall infection rates of between 8.7% and 14% have been reported, with lower rates in the upper extremity and higher rates in the lower extremity [2,7,[16][17][18][19]. Patients with proximal tibia replacements in particular are at high risk for periprosthetic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is not possible to avoid periprosthetic infection completely, despite the use of systemic antibiotic treatment, operating rooms with laminar airflow, and routine screening for methicillin-resistant Staphylococcus aureus (MRSA). In the literature, overall infection rates of between 8.7% and 14% have been reported, with lower rates in the upper extremity and higher rates in the lower extremity [2,7,[16][17][18][19]. Patients with proximal tibia replacements in particular are at high risk for periprosthetic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, similar indications and contraindications were used for surgical planning in both institutions, and criteria for failure assessed with similar intent, despite the differences inherent in implant design. In a large study by Jeys et al [13], including 228 distal femoral EPRs, aseptic loosening accounted for 13.6% of all failures with a median time to revision due to mechanical failure of 9.3 years. Moreover, Mittermayer et al [20] and Unwin et al [27] found, at 10 years postoperatively, 24% and 32.6%, respectively, of patients who had distal femoral EPR underwent revision for aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…37 The rate of infections varies according to the site of replacement with lower rates in upper extremities and higher rates in lower extremities. [39][40][41][42][43][44] However postsurgical infection is more common in pelvic tumor surgeries. Several authors have reported infection rates ranging from 12% to 47%.…”
Section: Custom-made Megaprosthesismentioning
confidence: 99%
“…Late prosthetic infections are associated with poor results when treated by lavage, debridement, and prolonged antibiotics administration 67 ; therefore, removal of infected prosthesis either as 1-or 2-stage procedure or an amputation becomes necessary. 42,[68][69][70][71] The reported success rate of eradicating infection with amputation ranges from 98% to 100%, 72% to 91% with 2-stage revision, and 42% with 1-stage revision. 70 However Allison et al 36 reported success rate of 42% with irrigation and debridement procedures alone (without any component exchange), 70% with single-stage irrigation and debridement procedure with the addition of modular component exchange and varying degrees of suppressive antibiotics, and in contrast to other studies formal two-staged implant removal, antibiotic spacer placement with subsequent reimplantation was associated with 62%.…”
Section: Custom-made Megaprosthesismentioning
confidence: 99%